2022
DOI: 10.3390/ijms232113115
|View full text |Cite
|
Sign up to set email alerts
|

The Blocking of Integrin-Mediated Interactions with Maternal Endothelial Cells Reversed the Endothelial Cell Dysfunction Induced by EVs, Derived from Preeclamptic Placentae

Abstract: Placental extracellular vesicles (EVs) have increasingly been recognized as a major mediator of feto-maternal communication. However, the cellular and molecular mechanisms of the uptake of placental EVs by recipient cells are still not well-understood. We previously reported that placental EVs target a limited number of organs in vivo. In the current study, we investigated the mechanisms underlying the uptake of placental EVs into target cells. Placental EVs were derived from explant cultures of normal or pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…These extracellular vesicles are enriched in anti-angiogenic factors, apoptosis-inducing ligands and active caspase 3, especially in early-onset pre-eclampsia 192,193 . Emerging evidence suggests that syncytiotrophoblast-released extracellular vesicles are internalized by endothelial cells, into which they release these factors and drive the maternal endothelial dysfunction and inflammation observed in pre-eclampsia 176,[194][195][196] .…”
Section: Dysregulated Placental Release Of Factorsmentioning
confidence: 99%
“…These extracellular vesicles are enriched in anti-angiogenic factors, apoptosis-inducing ligands and active caspase 3, especially in early-onset pre-eclampsia 192,193 . Emerging evidence suggests that syncytiotrophoblast-released extracellular vesicles are internalized by endothelial cells, into which they release these factors and drive the maternal endothelial dysfunction and inflammation observed in pre-eclampsia 176,[194][195][196] .…”
Section: Dysregulated Placental Release Of Factorsmentioning
confidence: 99%
“…To confirm that the EVs were derived from the syncytiotrophoblast, lysates of the micro‐EVs were demonstrated to contain cytokeratin a trophoblast marker (Figure S1d). Previously we have shown that micro‐EVs produced using this method are cytokeratin and CD63 positive but vimentin and calnexin negative and we have reported the proteome of these EVs 16,17 …”
Section: Resultsmentioning
confidence: 83%
“…To account for vesicles present in the FBS in media, we performed a negative control. For this, an equal volume of media was incubated with CMTPX dye at the concentration of 2.5 ng/mL in a 12‐well plate but without placental explants as published 16 . These FBS‐derived EVs will be referred to as EV vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…There is currently no consensus on the preferred uptake mechanism of specific EVs (Mathieu et al, 2019 ). This is specifically relevant during pregnancy, as the pathways of placental EV uptake in maternal organs are still underexplored (Cronqvist et al, 2020 ; Li et al, 2020 ; Feng et al, 2022 ). Also, placental EV uptake seems to be an energy- and size-dependent process with decreased uptake rates at low temperatures and slower uptake of large EVs, which might affect EV-mediated signaling in placental pathophysiologies (Feng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%